2013
DOI: 10.1038/mt.2013.118
|View full text |Cite
|
Sign up to set email alerts
|

Acat1 Knockdown Gene Therapy Decreases Amyloid-β in a Mouse Model of Alzheimer's Disease

Abstract: Both genetic inactivation and pharmacological inhibition of the cholesteryl ester synthetic enzyme acyl-CoA:cholesterol acyltransferase 1 (ACAT1) have shown benefit in mouse models of Alzheimer's disease (AD). In this study, we aimed to test the potential therapeutic applications of adeno-associated virus (AAV)-mediated Acat1 gene knockdown in AD mice. We constructed recombinant AAVs expressing artificial microRNA (miRNA) sequences, which targeted Acat1 for knockdown. We demonstrated that our AAVs could infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 45 publications
3
67
0
Order By: Relevance
“…In addition, Acat1 KD significantly diminished the oligomeric Aβ content in the brains of the 3XTg-AD mice [91]. These observations implicate that, in addition to its effect on reducing Aβ production, ACAT1 blockage may also promote the clearance of oligomeric Aβ.…”
Section: Acat1 Blockage On Aβ1-42 Degradation In Microgliamentioning
confidence: 64%
See 3 more Smart Citations
“…In addition, Acat1 KD significantly diminished the oligomeric Aβ content in the brains of the 3XTg-AD mice [91]. These observations implicate that, in addition to its effect on reducing Aβ production, ACAT1 blockage may also promote the clearance of oligomeric Aβ.…”
Section: Acat1 Blockage On Aβ1-42 Degradation In Microgliamentioning
confidence: 64%
“…These data are consistent with our earlier findings made in the Acat1 KO/3XTg-AD mice [77], supporting the conclusion that blocking ACAT1 is sufficient to benefit AD. The result of Murphy et al [91] also demonstrated that after the AD onset, partial inactivation of ACAT1 (~40%) in the brain was sufficient to cause a decrease in the levels of Aβ1-42 in the 3XTg-AD mice.…”
Section: Genetic Ablation Of Acat1 In Ad Micementioning
confidence: 92%
See 2 more Smart Citations
“…Cholesterol turnover and biology has been linked to AD based on circumstantial evidence (summarized from Chang et al, 2010;Bryleva et al 2010;Murphy et al, 2013), including observations that inhibition or knockdown of ACAT-1 in mice can result in reduced accumulation of amyloid peptides accompanied by ameliorated cognitive defects. However the mechanism and role of ACAT-1 in this process is a matter for speculation and ongoing research.…”
Section: Role Of Acat In Gallstone Formationmentioning
confidence: 99%